2010
DOI: 10.1111/j.1442-2042.2010.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal mass sampling: An enlightened perspective

Abstract: Renal mass sampling (RMS) can be carried out by core biopsy or fine needle aspiration with each presenting potential advantages and limitations. The literature about RMS is confounded by a lack of standardized techniques, ambiguous terminology, imprecise definitions of accuracy, substantial rates of non-informative biopsies, and recurrent diagnostic challenges with respect to eosinophilic neoplasms. Despite these concerns, RMS has an expanding role in the evaluation and treatment of renal masses, in order to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 120 publications
(307 reference statements)
2
25
0
Order By: Relevance
“…We found repeat biopsy can potentially lead to diagnosis in 80% of patients with initially nondiagnostic results. The nondiagnostic rate was similar to the previously reported range of 10% to 20%, 6 but the rate of malignancy at extirpation among nondiagnostic biopsies has not been previously reported to our knowledge. Also, relative to prior reviews of the literature, we excluded series with large renal masses that were not stated to be localized, as well as biopsy studies before ablation procedures.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We found repeat biopsy can potentially lead to diagnosis in 80% of patients with initially nondiagnostic results. The nondiagnostic rate was similar to the previously reported range of 10% to 20%, 6 but the rate of malignancy at extirpation among nondiagnostic biopsies has not been previously reported to our knowledge. Also, relative to prior reviews of the literature, we excluded series with large renal masses that were not stated to be localized, as well as biopsy studies before ablation procedures.…”
Section: Discussionsupporting
confidence: 71%
“…The limitation of the literature has been previously acknowledged but addressed for the first time in the current systematic review by cross tabulating raw data from individual studies. 6 For the clinically relevant scenario of a patient with a renal mass biopsy result, a positive biopsy was associated with a high PPV compared to the gold standard, indicating strong confidence in a positive result. On the other hand, a negative biopsy result led to greater uncertainty with 36.7% of those undergoing extirpation found to have malignant disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 Even though the diagnostic accuracy is progressively improving, according to the current recommendations not all patients with SRM are ideal candidates to RTB, but only those patients in which a percutaneous biopsy is going to impact the future clinical management. 14,35 In these different scenarios, RTB could reduce the morbidity of unnecessary procedures and, in contrast, maximize treatment effectiveness. To date, the currently available series underline the feasibility and safety of active surveillance for cT1a RCC, but very little is known about the natural history of such tumors that have remained on AS for a long period.…”
Section: Evidence Analysis As For Renal Tumors ≤4 CM (Srm)mentioning
confidence: 99%
“…[38][39][40] In a comprehensive meta-analysis of 10 studies from nine single-institutional series, Chawla et al reported outcomes of 234 expectantly managed SRM. 11 The evaluated series included six to 40 patients, with a mean follow up of 34 months (median 32, range [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In all series combined together, the mean tumor size at presentation was 2.6 cm (median 2.48 cm), and the mean linear growth rate was 0.28 cm/year.…”
Section: Evidence Analysis As For Renal Tumors ≤4 CM (Srm)mentioning
confidence: 99%